Venture Capital Market in China: A New Approach to Innovation Management - RESHETNIKOVA, Marina (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this work is to conduct an evidence-based analysis of the Chinese venture capital market current state and assess the reality of the scenario like heating the market to a new crunch. As a result, the article proves that the main reason for the avalanche-like acceleration of growth in the Chinese venture capital market was miscalculations in the actions of the Government addressed to pay off the problems in the domestic stock market in 2015. The article proves that, despite signs of overheating, it is still premature to talk about the formation of a "bubble" in the venture capital market. RESUMEN El propósito de este trabajo es llevar a cabo un análisis basado en la evidencia del estado actual del mercado de capital de riesgo chino y evaluar la realidad del escenario como calentar el mercado a una nueva crisis. Como resultado, el artículo demuestra que la razón principal de la aceleración del crecimiento similar a una avalancha en el mercado de capital de riesgo chino fue un error de cálculo en las acciones del Gobierno dirigidas a saldar los problemas en el mercado de valores interno en 2015. El artículo demuestra que, a pesar de los signos de sobrecalentamiento, todavía es prematuro hablar sobre la formación de una "burbuja" en el mercado de capital de riesgo.